What Matters Most for Teacher Policies : A Framework Paper - World Bank (Washington, DC, 2014)
Over the past decade, both developed and developing countries have become growingly concerned with how to raise the effectiveness of teachers. The growing focus on the need to strengthen the teaching profession to ensure better education results has encountered the problem that evidence on the policies that raise teaching quality is scattered, incomplete and, in some cases, presents contradictory findings. This paper provides a framework for analyzing teacher policies in education systems around the world in order to support informed education policy decisions. It provides a lens through which governments, World Bank staff, and other interested parties can focus the attention on what the relevant dimensions regarding teacher policies are, what teacher policies seem to matter most to improve student learning, and how to think about prioritization among competing policy options for teacher policy reform. The systems approach for better education results (SABER) - teachers initiative aims to collect, analyze, synthesize, and disseminate comprehensive information on teacher policies across countries around the world. The focus of the paper is the description of the conceptual framework to analyze and assess teacher policies, as well as a review of the evidence base that supports it. The document is organized as follows: section one provides an overview of the general approach, main components, and objectives of the framework, as well as an explanation of the evidence base that supported its development. Section two focuses on the first component of the framework, and describes the categories that are relevant to produce a comprehensive descriptive account of the teacher policies that are in place in a given education system. Section three focuses on policy guidance. Section four concludes presenting an account of how the framework is expected to evolve as new evidence on teacher policies becomes available.